Care recommendations for parturient and postpartum women and newborns during the COVID-19 pandemic: a scoping review - Victor Hugo Alves Mascarenhas; Adriana Caroci-Becker; Kelly Cristina Máxima Pereira Venâncio; Nayara Girardi Baraldi; Adelaide Caroci Durkin; Maria Luiza Gonzalez Riesco (Universidade de São Paulo, 2020)
Objective to map the current knowledge on recommendations for labor, childbirth, and newborn (NB) care in the context of the novel coronavirus. Method scoping review of papers identified in databases, repositories, and reference lists of papers included in the study. Two researchers independently read the papers' full texts, extracted and analyzed data, and synthesized content. Results 19 papers were included, the content of which was synthesized and organized into two conceptual categories: 1) Recommendations concerning childbirth with three subcategories - Indications to anticipate delivery, Route of delivery, and Preparation of the staff and birth room, and 2) Recommendations concerning postpartum care with four categories - Breastfeeding, NB care, Hospital discharge, and Care provided to NB at home. Conclusion prevent the transmission of the virus in the pregnancy-postpartum cycle, assess whether there is a need to interrupt pregnancies, decrease the circulation of people, avoid skin-to-skin contact and water births, prefer epidural over general anesthesia, keep mothers who tested positive or are symptomatic isolated from NB, and encourage breastfeeding. Future studies are needed to address directed pushing, instrumental delivery, delayed umbilical cord clamping, and bathing NB immediately after birth.